EU Policies to Combat the Energy Crisis - PAUL CALANTER; DANIELA ZISU (Global Economic Observer)
The European Union is facing a complex geopolitical crisis, which represents a threat to its energy security. Having this in mind, EU must redouble its efforts to become energy independent, focusing on renewable energy. In the following paper, we intend to analyze the measures that the Union wants to take in order to combat the energy crisis. Therefore, it will be analyzed the situation of nuclear energy and natural gas in the EU, given that these were the two technologies with the greatest contribution to electricity generation. At the same time, in the paper we will examine the REPowerEU plan, which the Commission wants to develop, in order to support sources of electricity supply, improve energy efficiency and to make the switch to renewable energy faster. The purpose of these actions is to gradually eliminate gas imports from the Russian Federation and also the EU's dependence on fossil fuels and would function as an insurance against the shocks of prices. Also, at the end of the paper, we will expose small-scale energy solutions that can be applied in residential areas but also largescale solutions that can significantly contribute to reducing dependence on fossil fuels.